Health‐related quality of life in patients with lower rectal cancer after sphincter‐saving surgery: a prospective 6‐month follow‐up study. (25th November 2015) - Kinoshita, Y.; Nokes, K.M.; Kawamoto, R.; Kanaoka, M.; Miyazono, M.; Nakao, H.; Chishaki, A.; Mibu, R.
Abstract : This longitudinal descriptive study examined whether rectal cancer patients report changes in health‐related quality of life (HRQOL) over a 6‐month period after different types of sphincter‐saving surgery (SSS): intersphincteric resection (ISR), ultra‐low anterior resection (ULAR) and low anterior resection (LAR). It also compares HRQOL among the three groups of patients. Seventy‐three patients from two hospitals in Japan completed questionnaires on HRQOL and defecation symptoms immediately before surgery and 1 and 6 months afterwards. Results showed that ISR patients had significantly worse HRQOL scores than ULAR and LAR patients and more defecation symptoms that persisted during the 6 months post‐SSS. Thus, patients undergoing ISR require psychological and social support, including skills in competent self‐management, during the early post‐operative period. Furthermore, defecation problems substantially influence HRQOL. The first month post‐SSS is particularly challenging. The assumption that HRQOL is better after SSS compared to living with a permanent stoma might not be valid.